2023
DOI: 10.1038/s41467-023-42622-7
|View full text |Cite
|
Sign up to set email alerts
|

TDP1 suppresses chromosomal translocations and cell death induced by abortive TOP1 activity during gene transcription

Diana Rubio-Contreras,
Fernando Gómez-Herreros

Abstract: DNA topoisomerase I (TOP1) removes torsional stress by transiently cutting one DNA strand. Such cuts are rejoined by TOP1 but can occasionally become abortive generating permanent protein-linked single strand breaks (SSBs). The repair of these breaks is initiated by tyrosyl-DNA phosphodiesterase 1 (TDP1), a conserved enzyme that unlinks the TOP1 peptide from the DNA break. Additionally, some of these SSBs can result in double strand breaks (DSBs) either during replication or by a poorly understood transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…We previously reported that TDP1 is required for the repair of TOP1-induced DSBs in quiescent hTERT-immortalized retinal pigment epithelial cells (RPE-1) cells(19). To evaluate possible TOP1-induced DSB repair defects in TDP1-associated neurological disease SCAN1, we conducted complementation experiments on TDP1 -/- RPE-1 cells with an empty vector (EV), a wild-type TDP1 or the SCAN1-associated mutation H493R (hereafter TDP1 H493R ) which were under the control of a doxycycline-inducible promoter (see methods for details).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that TDP1 is required for the repair of TOP1-induced DSBs in quiescent hTERT-immortalized retinal pigment epithelial cells (RPE-1) cells(19). To evaluate possible TOP1-induced DSB repair defects in TDP1-associated neurological disease SCAN1, we conducted complementation experiments on TDP1 -/- RPE-1 cells with an empty vector (EV), a wild-type TDP1 or the SCAN1-associated mutation H493R (hereafter TDP1 H493R ) which were under the control of a doxycycline-inducible promoter (see methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…1b). We have previously shown that CPT-induced DSBs under these conditions are entirely dependent on gene transcription(19). Importantly, expression of wild-type TDP1 suppressed the accumulation of CPT-induced DSBs to a much greater extent than TDP1 H493R , which remained close to the levels observed with EV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations